Validation of Hospital Administrative Dataset for adverse event screening. Issue 5 (27th April 2010) - Verelst, Sandra; Jacques, Jessica; Van den Heede, Koen; Gillet, Pierre; Kolh, Philippe; Vleugels, Arthur; Sermeus, Walter
Abstract : Objective: To assess whether the Belgian Hospital Discharge Dataset (B-HDDS) is a valid source for the detection of adverse events in acute hospitals. Design, setting and participants: Retrospective review of 1515 patient records in eight acute Belgian hospitals for the year 2005. Main outcome measures: Predictive value of the B-HDDS and medical record reviews and degree of correspondence between the B-HDDS and medical record reviews for five indicators: pressure ulcer, postoperative pulmonary embolism or deep vein thrombosis, postoperative sepsis, ventilator-associated pneumonia and postoperative wound infection. Results: Postoperative wound infection received the highest positive predictive value (62.3%), whereas postoperative sepsis and ventilator-associated pneumonia were rated as only 44.2% and 29.9% respectively. Excluding present on admission from the screening substantially decreased the positive predictive value of pressure ulcer from 74.5% to 54.3%, as pressure ulcers present on admission were responsible for more B-HDDS-medical record mismatches than any other indicator. Over half (56.8%) of false-positive cases for postoperative sepsis were due to a lack of specificity of the ICD-9-CM code, whereas in 58.6% of false-positive cases for ventilator-associated pneumonia, clinical criteria appeared to be too stringent. Conclusions: The B-HDDS has the potential to accurately detect some but not all adverse events. Adding a code 'present on admission' and improving the ICD-9-CM codes might already partially improve the correspondence between the B-HDDS and the medical record review.